Speech by the Honourable the Chief Minister,Penang ,at the laying of the Foundation Stone Ceremony of the St. John Ambulance of Malaysia , State of Penang , Headquarters Building at Grove Road, Penang, on Saturday 16th October 1976 at 4.30 p.m. - Lim, Chong Eu (1976)
I am greatly privileged to be invited by the Officers and Members of St. John Ambulance of Malaysia State of Penang to attend this auspicious occasion of the laying of the Foundation Stone Ceremony of your new headquarters building.